A lexical didactic procedure to develop lexical competence in university students (2025)
Lexical knowledge is fundamental to language learning, enhancing not only communication skills but also academic performance and personal growth. English, with approximately 114,000- word families, presents a significant challenge for EFL students. These learners must learn not only individual words but also formulaic expressions, such as collocations, phrasal verbs, idioms, and fixed expressions, to communicate effectively. Research underscores the importance of systematic and intentional lexical instruction to help students optimize their learning, expand their lexical knowledge, and develop strategies for becoming autonomous and proficient language users. This study aimed to analyze the teaching and learning of lexis among 4th-semester students in a teacher education program at a public university in Puerto Colombia, with the goal of identifying ways to improve these processes in this specific context. To achieve this, I conducted a comprehensive review of key constructs such as teaching, learning, didactics, curriculum, communicative competence, lexical competence, lexis assessment, the Four Strands Approach, and lexical knowledge. Based on this review, I designed a Lexical Didactic Procedure (LDP). The study followed an Educational Action Research (EAR) design. I was developed at Universidad del Atlántico, with (n=22) 4th-semester students enrolled in the Taller de Lengua y Cultura Inglesa course, along with the teacher-researcher, and three colleagues. Data collection methods included document analysis, self-observations, semi-structured interviews, field notes, a questionnaire, and pre- and post-tests. I applied these instruments in two phases: diagnostic and implementation. The analysis in the diagnosis revealed that there was no research-based procedure to teach lexis systematically and effectively, which could aid learners in expanding and consolidating their lexical knowledge. Therefore, it was necessary to design a Lexical Didactic Procedure (LDP) to address this gap in teaching and learning lexis, incorporating recycling, mental processing, and assessment activities as integral parts of it. The implementation of the Lexical Didactic Procedure (LDP) proved beneficial, enabling the systematic recycling of target lexis and promoting its consolidation in the long-term memory of the target group. This procedure facilitated the enhancement of their productive lexical knowledge, ultimately strengthening their overall lexical competence. The study highlights the importance of structured lexical instruction in improving EFL learners' lexis skills, focusing on methods like the Lexical Didactic Procedure (LDP). It shows that with the right approach, learners can make significant progress in both understanding and using words effectively, with productive lexis improving faster than expected. The findings also stress the value of teaching collocations, raising awareness of lexis learning, and boosting student motivation. Recycling lexis and engaging in meaningful mental activities are key to helping learners remember and use new words. The practical implications include integrating the LDP into language courses, preparing teachers through workshops, designing balanced syllabi, adapting to specific teaching contexts, and encouraging learners to become more independent. These strategies provide a clear path for educators to help them build stronger lexis skills and improve overall language proficiency. Consequently, this study provides valuable insights into the field of English Language Teaching (ELT) in Colombia, particularly in lexical instruction.